Call Centre Influence on the Delivery of Mental Health Services Among Young People: A Case of One2one Call Centre in Nairobi County - Mutwiri, Robert Kimathi; Kawila, Caroline; Olouch, Musa (International Journal of Health Sciences, 2024)
Purpose: The purpose of this study was to examine the influence of call centers on the delivery of mental health services among young people in Nairobi County. Specifically, the study aimed to investigate the impact of crisis intervention, round-the-clock availability, resource sharing, and follow-ups on mental health service delivery. Methodology: The study employed a descriptive-cross-sectional research design to assess the impact of call centers on mental health service delivery. The target demographic consisted of healthcare providers affiliated with the one2one Call Centre in Nairobi County. A sample size of 112 respondents was selected using basic random selection methods. Data was collected through the distribution of questionnaires, and Statistical Package for Social Science (SPSS) version 25 was utilized for data analysis. Descriptive statistics such as mean, standard deviation, frequencies, and percentages were employed, along with correlation and regression analysis to evaluate the relationships between research variables. Findings: The study found that crisis intervention, round-the-clock availability, and resource sharing had a positive impact on the delivery of mental health services among young people in Nairobi County. Specifically, crisis intervention strategies were shown to significantly enhance the overall mental health support system, ensuring timely assistance for young individuals in need. Furthermore, maintaining round-the-clock availability allowed service providers to cater to the diverse needs and schedules of young people seeking assistance, thereby improving the overall delivery of mental health services across the county. Unique Contribution to Theory, Practice, and Policy: This study makes several contributions to theory, practice, and policy in the field of mental health service delivery. Firstly, it adds to the body of literature on the effectiveness of call centers in enhancing accessibility and reachability of mental health services, particularly among young people. Secondly, the findings provide valuable insights for healthcare practitioners and policymakers on the importance of crisis intervention, round-the-clock availability, and resource sharing in improving mental health service delivery.